Increased Neurovascular Morbidity Is Seen in Documented Knee Dislocation Versus Multiligamentous Knee Injury. (19th May 2021) - Kahan, Joseph B.; Schneble, Christopher A.; Li, Don; Petit, Logan; Huang, Patrick; Bullock, James; Porrino, Jack; Richter, Dustin L.; Schenck, Robert C.; Medvecky, Michael J.
Abstract : Update: This article was updated on May 19, 2021 because of previous errors, which were discovered after the preliminary version of the article was posted online. In the legend for Figure 3-A, the phrase that had read "T1-weighted coronal MRI showing a right knee" now reads "T1-weighted coronal MRI showing a left knee." On page 924, in the section entitled "Materials and Methods, " the sentence that had read "If there was no radiographic evidence or if there was a clinical note that documented visible deformity around the knee with no reduction maneuver being performed, then the patient was classified into the non-dislocated MLKI group." now reads "If there was no radiographic evidence or if there was no clinical note that documented visible deformity around the knee with no reduction maneuver being performed, then the patient was classified into the non-dislocated MLKI group." On page 925, in the section entitled "Analysis, " the sentence that had read "Our study included 78 dislocated MLKIs and non-dislocated MLKIs, so both cohorts were adequately powered for the overall analysis." now reads "Our study included 45 dislocated MLKIs and 78 non-dislocated MLKIs, so both cohorts were adequately powered for the overall analysis." Finally, on page 927, in the section entitled "Discussion, " the sentence that had read "Interestingly, we found that MLKIs with a documented knee dislocation had a substantially higher rate of vascular injury (23%) compared with those without (3%)." now reads "Interestingly, we found that MLKIs with a documented knee dislocation had a substantially higher rate of vascular injury (18%) compared with those without (4%)." Background: The terms "knee dislocation" and "multiligamentous knee injury" (MLKI) have been used interchangeably in the literature, and MLKI without a documented knee dislocation has often been described as a knee dislocation that "spontaneously reduced." We hypothesized that MLKI with documented tibiofemoral dislocation represents a more severe injury than MLKI without documented dislocation. We aimed to better characterize the injuries associated with documented knee dislocations versus MLKIs without evidence of tibiofemoral dislocation. Methods: A total of 124 patients who were treated for an MLKI or knee dislocation to a single level-I trauma center between January 2001 and January 2020 were retrospectively reviewed. Patients were stratified into 2 groups, those with and those without a documented knee dislocation, and 123 of 124 patients were included in the analysis (78 in the non-dislocated group and 45 in the dislocated group). Data regarding patient demographics, injury pattern, and associated neurovascular injury were collected and compared between groups. Results: Dislocated MLKIs, compared with non-dislocated MLKIs, had higher rates of peroneal nerve injury (38% versus 14%, respectively; p = 0.004), vascular injury (18% versus 4%; p = 0.018), and an increased number of medial-sided injuries (53% versus 30%; p = 0.009). There was no difference between dislocated and non-dislocated MLKIs in the number of bicruciate ligament injuries (82% versus 77%, respectively; p = 0.448), or lateral-sided injuries (73% versus 74%; p = 0.901). Conclusions: Dislocated MLKIs were found to have increased rates of neurovascular injury compared with non-dislocated MLKIs, suggesting that knee dislocation and MLKI may not be synonymous in terms of associated injuries. Not all MLKIs are the result of a knee dislocation, and thus a documented tibiofemoral dislocation is a distinct entity that carries a greater risk of neurovascular compromise. We propose that these terms not be used interchangeably as previously described, and also that a high degree of vigilance must be maintained to evaluate for potential limb-threatening neurovascular injuries in any type of MLKI. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.